Penggunaan gambar sebagai media pembelajaran telah terbukti efektif dalam meningkatkan pemahaman siswa terhadap mata pelajaran Biologi - Febryandi Mukti; Nadya Wahyu Ratnawati; Hasyim Burhani (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2024)
This research discusses the use of images as an effective learning medium in increasing students' understanding of Biology subjects. The use of images in a learning context can help students visualize abstract and complex concepts in Biology, thereby facilitating a more interactive and easy-to-understand learning process. This method can stimulate students' interest in learning Biology, strengthen information retention, and improve their problem solving skills in the context of natural sciences. This research illustrates the significance of using images as a learning tool that can support the achievement of Biology learning objectives.